Analisis Pendapatan Agroindustri Ubi Kayu Di Kabupaten Deli Serdang, Indonesia - RAHMANTA GINTING; Elisabet Siahaan; Samsuri; Remus Hasiholan (JURNAL AGRICA, 2023)
One of the empowerment of micro small businesses carried out by the Regional Government of Deli Serdang is the utilization of cassava as a raw material for agroindustry which has the potential to be developed and has a profitable market potential for MSMEs. In order to increase income, as one of the government's policies, namely increasing the agro-industry program. In this program, cassava farming and its agro-industry provide an opportunity to be an alternative choice. This can be done because of the advantages possessed by cassava plants, namely besides having a relatively high adaptability and relatively easier farming, and also various benefits, both for food and non-food. The purpose of this study was to determine the cost structure, acceptance, income, and feasibility of processing cassava into opaque. This study used a sampling method in the form of a census on cassava agro-industry, with all respondents processing cassava into opaque craftsmen as many as 35 people. Methods of data collection using questionnaires and field observations. The data analysis tool used is the analysis of the structure of costs, revenues, revenues and R/C. The results of the research show that variable costs are the biggest costs compared to other costs. The average cost of production incurred by MSMEs is IDR 293,071,511 per month, the average income is IDR 318,000,000 per month and the average income is IDR. 24,928,489 per month, with an R/C ratio of 1.08 which means that the cassava agro-industry is profitable or feasible to develop in the research area